1997
DOI: 10.1016/s0006-3495(97)78784-8
|View full text |Cite
|
Sign up to set email alerts
|

Refractive indices of the collagen fibrils and extrafibrillar material of the corneal stroma

Abstract: Ultrastructural data from x-ray diffraction studies of the cornea were used to estimate the refractive indices of the collagen fibrils and extrafibrillar material of human, ox, trout, and rabbit corneas. X-ray diffraction measurements of the size and spacing of the collagen fibrils and the separation between the constituent molecules of the fibrils were taken from a previous species study. The tissue volume fractions occupied by the stromal components were estimated and their refractive indices were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 24 publications
2
78
0
1
Order By: Relevance
“…The refractive index of the hydrated collagen fibrils, the refractive index of the interfibrillar matrix, and the ratio of these have previously been obtained using X-ray diffraction measurements in a number of different species. 2 The relative positions of the individual fibrils, and the diameter of each fibril, are obtained from electron micrographs. There is a problem in using measurements from electron microscopy in that it has been shown that a number of microscope preparation protocols result in considerable shrinkage of fibril diameters and, particularly, interfibril spacings.…”
Section: Direct Summation Of Fields Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The refractive index of the hydrated collagen fibrils, the refractive index of the interfibrillar matrix, and the ratio of these have previously been obtained using X-ray diffraction measurements in a number of different species. 2 The relative positions of the individual fibrils, and the diameter of each fibril, are obtained from electron micrographs. There is a problem in using measurements from electron microscopy in that it has been shown that a number of microscope preparation protocols result in considerable shrinkage of fibril diameters and, particularly, interfibril spacings.…”
Section: Direct Summation Of Fields Methodsmentioning
confidence: 99%
“…Also, recent X-ray diffraction data have unambiguously confirmed earlier evidence for a difference in the refractive indices of the collagen fibrils and of the extrafibrillar material. 2 Most modern models are based on the lattice theory put forward by Maurice. 3 By approximating the collagen fibril to perfect, infinitely long cylinders, an estimate of the scattering from an individual fibril can be calculated.…”
Section: Corneal Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering particles (organelles, protein fibrils, membranes, and globules) have greater density of proteins and lipids and, hence, higher refractive index (n s = 1.39-1.47) in comparison with the base substance of the cytoplasm [6]. The refractive index values of the connective tissue fibrils lie in the range 1.41-1.53 and depend upon the degree of hydration of their major component, the collagen [9]. The refractive index of the interstitial fluid and the blood plasma amounts to nearly 1.33-1.35 depending on the wavelength [3,10].…”
Section: Introduction: Fundamentals Of Optical Clearing Of Tissues Anmentioning
confidence: 99%
“…The significant deviation of the actual n g (C w ) curve from this approximating line in the region C w ≤ 0.52 may be attributed to a change of the mode of hydration. In the literature, two modes of collagenous tissue hydration are distinguished [33][34][35][36]. For relatively high values of H (H > H c , where H c is a critical value, the so-called fibrillar saturation point [35]), changes in the total water content in the tissue lead to changes of the water content in extrafibrillar space while the water content in collagen fibrils remains unchanged [7,[33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%